Toksisitas Akut Ekstrak Etanol Daun Jambu Bol (Eugenia malccensis L.) - Helmi Arifin; Novika Maulina; Zet Rizal (STIFARM Padang, 2009)
The research of acute toxicity of the etanolic extract of the leave of Jambu Bol (Eugenia malaccencis L.) has been done. Parameter measure were LD50 and the delay toxic effect during 14 day observation covering body weight, water intake, urine output, and relative weight of the liver, heart, and kidney. The toxicity by oral administration of the leave of Jambu Bol (Eugenia malaccencis L.) with dose 16 g/kg BB. that showed the etanolic extract of leave Jambu Bol (Eugenia malaccencis L.) is practical not toxic category (LD50 > 15 g/kg BB). The delay toxic effect was seen by significant changes in body weight and water intake, and was not see significant changes in urine output and the relative weight.